Фермент пероксидаза – універсальний маркер зимостійкості рослин - Kapustian, A.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The methods of prediction of winter-resistance of plants are offered which are based on the property of the enzyme peroxidase to increase activity at a low-temperature stress.